(untitled) (Basel Institute on Governance Working Papers, 2023)
The Working Paper presents the results of a nationwide survey of 1,209 individuals in Bulgaria, conducted in February to early March 2023. The survey examined how corruption is perceived in Bulgaria by different types of respondent, and what kind of behaviour is considered acceptable. It also looked at respondents’ perceptions of anti-corruption efforts and under which circumstances they would be more likely to report corruption to the authorities.